Apoio social, mutualidade entre os pais e qualidade de vida relacionada à saúde das cuidadoras de crianças com necessidades especiais de saúde - Baldini, Paula Rossi (Universidade Federal de São Carlos, 2020)
Objective: to analyze the influence of social support received and parental mutuality on the health-related quality of life of caregivers of children with special health needs. Method: observational, analytical, cross-sectional, quantitative study. Caregivers of children with special health needs over 18 years of age who lived with a partner were eligible. The use of psychoactive substances (alcohol and other drugs) was an exclusion criterion. It followed ethical procedures for research involving human subjects. Data collection was performed between November 2018 and March 2019 by applying an online form. The online form included the following instruments: sociodemographic characterization instrument, Medical Outcomes Study 36-Item Short Form, Social Support Scale and Family Management Measure (only the subscale parental mutuality). For statistical analysis, were used the Spearman’s Correlation and univariate and multivariate linear regression analysis. Results: 181 caregivers participated, with average age of 31.5 years. Among the eight domains of health-related quality of life, vitality and emotional aspects were the domains that had the lowest score (53.2 and 56.1 respectively). Regarding the social support received, the five dimensions had satisfactory scores, above 80 points. The average total score for parental mutuality was 30.8, indicating a satisfactory perception of how the couple shares decisions regarding child care. In the multivariate regression analysis, the following statistically significant associations were maintained: information dimension of social support and the domains pain, mental health, social aspects and general health status of health-related quality of life (p = <0.001); material dimension (social support) and general health status (p = 0.034); emotional dimension (social support) and vitality (p = <0.001); parental mutuality and the domains of pain, social aspects and emotional limitations of health-related quality of life (p = <0.001, 0.003, 0.002, respectively). Conclusions: the social support received and the parental have a positive influence in some domains of health-related quality of life. It is important to plan actions to strengthen mutuality and the social support received.
Social support, parental mutuality and health-related quality of life for caregivers of children with special health needs
Keywords: Cuidadores; Qualidade de vida relacionada à saúde; Apoio social; Relações familiares; Enfermagem pediátrica; Pediatric nursing; Caregivers; Health-related quality of life; Social support; Family relations; CIENCIAS DA SAUDE::ENFERMAGEM